Early pharmaceutical evaluation of a crystalline and hygroscopic GABAB receptor agonist. (October 2013) - Sigfridsson, Kalle; Andersson, Thomas; Berntsson, Veronica; Wang, Yudong
Abstract : Lesogaberan is a potent gamma amino butyric acid agonist and has been evaluated for its utility in treatment of gastroesophageal reflux disease. Lesogaberan is a crystalline substance that absorbs considerable amounts of water above 65% relative humidity (RH) where it also liquifies. As a result of the hygroscopicity of the zwitterionic form an investigation of different salt forms was performed. Since the test compound is polar and lacks ultraviolet (UV) chromophore, conventional separation and detection techniques could not be used to characterise the test compound and the impurities. The analytical techniques are described, focusing on the capillary electrophoresis method with indirect UV detection for purity, the liquid chromatographic method for enantiomeric separation with derivatisation with UV chromophore and two complementary nuclear magnetic resonance (NMR) approaches ( 19 F-NMR and 1 H-NMR) for impurities. The stability study in solution showed that solutions between pH 5 and 7 were the most stable ones, but after some time degradation occurred at room temperature. When bulk lesogaberan was stored at 25°C/60% RH no chemical degradation was observed after 1 year. At 40°C/75% RH, where the compound liquefies, a significant degradation was observed after 1 month. However, in a closed container (= 40°C) or as a napsylate salt, no degradation of lesogaberan was observed at 40°C/75% RH.